Complex nature of humanitarian crisis: Unique dynamics of civil military relations in Nepal - Khatri, Ratindra (Unity Journal, 2020)
The Nepali Army in its vital role in humanitarian assistance and disaster response operation in Nepal receives reputation the world wide. Nepal is prone to disaster risk and the majority of people are living in vulnerable situation. Every year Nepal is facing different types of disasters that caused massive loss of lives and properties. Nepal has not been able to prepare any other viable alternatives in the civil society, so there is no other choice than utilizing military or security forces during any disasters. The Nepali Army has vast inbuilt resources to mobilize its troops effectively in any parts of the country. However, timely and effective disaster response is very difficult due to numerous constraints and complexities. Difficult terrain, limited road communication, inadequate resources and insufficient response capacity are prime reasons that make response operations very challenging. The Army together with other security agencies is performing role as per the given mandate articulated in act, rules, framework and guidelines. In this situation, building civil-military coordination mechanism can be an effective means to respond to the disaster. As a matter of fact, a comprehensive disaster army should continue dialogue, training and exercise with foreign militaries for better understanding and learning through experience. Despite the Nepali Army’s spectacular capability to disaster response, there is a debate whether the military is a right institution to involve in the humanitarian response operations. However, keeping in mind Nepal’s reality without compromising primary role of national sovereignty, territorial integrity and national independence, the Nepali Army should enhance its capability to save lives and property from disasters and hazards.